Growth form and fruit and flower numbers of plants on Kilimanjaro - Maximilian Vollstaedt; Matthias Schleuning; Katrin Böhning-Gaese (PANGAEA, 2018)
This dataset includes the identities of all fruiting and flowering plants on all study sites sampled for mutualistic interactions (i.e. all except for Hel and Fer). We identified plants to species level, and recorded some general information on size and growth form (e.g. tree, shrub, liana). Additonally, we counted the number of fruits and flowers on each plant individual to estimate crop size.